#### Answer

-3$x^{2}$

#### Work Step by Step

5$x^{2}$ - 8$x^{2}$
= (5-8)$x^{2}$ (combine like terms)
=-3$x^{2}$

Published by
Pearson

ISBN 10:
0321867327

ISBN 13:
978-0-32186-732-2

-3$x^{2}$

5$x^{2}$ - 8$x^{2}$
= (5-8)$x^{2}$ (combine like terms)
=-3$x^{2}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.